Kompetensi Pedagogik Guru Pendidikan Anak Usia Dini dalam Pengelolaan Pembelajaran di Taman Kanak-Kanak Alam Muara Bungo - Kurniasari, Anita; Ridwan, Ahmad; shalahudin (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2022)
Early Childhood Education (PAUD) is a period of learning that will take effect to the children’s development and their futures. One of the components that are able to influence the success of achieving goals of the PAUD is the Human Resources or teachers. These study aims to determine the teachers’ pedagogic competence in learning management of kindergarten Alam Muara Bungo. This study uses a descriptive qualitative approach with observation, interview and documentation. The technique of analysis data is using the Miles and Huberman and Creswell model, namely credibility, transferability, dependability, and confirmability. The results showed that the learning management of kindergarten Alam Muara Bungo was carried out by models are (1) Planning is the structuring of management in learning implementation, (2) Learning implementation is scientific-based learning that is implemented by concept of moral pillars, leadership pillars, business pillars and logic pillars, (3) Learning assessment that have structured and scheduled. These shows that the teacher’s pedagogic competence of kindergarten Alam Muara Bungo in learning management is categorized that they have a good competence. They also have mastered and implemented the four components of pedagogic competence, namely practice teaching, observation of teaching and learning, theory or theoretical knowledge of teaching and student learning, and planning of teaching. Although the teachers have a good pedagogic competence in learning management, however the head master and human resource manager of the Bungo Master Foundation continue to improve their teachers’ competence by programs are 1) coaching, 2) education and training, and 3) recruitment of qualified teachers.